2019
DOI: 10.1002/cae.22178
|View full text |Cite
|
Sign up to set email alerts
|

An interactive virtual laboratory addressing student difficulty in differentiating between chemical reaction kinetics and equilibrium

Abstract: The Reaction Rate vs Equilibrium Interactive Virtual Laboratory (IVL) has been developed to address a common student misconception in analyzing and designing chemical reactors—the difference between reaction kinetics and reaction equilibrium. The IVL allows students to make meaning of the difference between reaction rate and equilibrium by exploring their dependence on temperature. The design is to create a cognitive conflict between their observations of how reaction rate and equilibrium depend on temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
10
2
Order By: Relevance
“…When students were asked if they would have performed better if they had developed the activity alone, only 17.6% answered positively (no significant difference was found between TBL-Groups and PI-Groups students). The students perceived the collaborative work in this environment as an opportunity to make progress, as reported by Koretsky . However, PI-Group students reported that they had more opportunities to contribute to the group effort, due to the reduced number of members in the groups.…”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…When students were asked if they would have performed better if they had developed the activity alone, only 17.6% answered positively (no significant difference was found between TBL-Groups and PI-Groups students). The students perceived the collaborative work in this environment as an opportunity to make progress, as reported by Koretsky . However, PI-Group students reported that they had more opportunities to contribute to the group effort, due to the reduced number of members in the groups.…”
Section: Resultscontrasting
confidence: 97%
“…Experiences in developing chemical kinetics concepts during the COVID-19 pandemic are also interesting to report here. Virtual laboratories were proposed as interactive experiences to understand concepts of chemical kinetics and an opportunity to work collaboratively . Other studies explored students’ experience during the pandemic to develop concepts of chemical kinetics: making analogies between social distancing and the collision cross section of a chemical reaction and between virus propagation and second-order reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial introductions of the VL concepts, research on the effectiveness of VLs confirmed that properly designed virtual simulation tools can enhance students' learning processes [9], [10]. As a result, VLs have been implemented and/or studied across the wide variety of disciplines, such as life science (e.g., biology) [11], [12], [13], [14], [15], physical sciences (e.g., physics and chemistry) [16], [17], [18], [19], [20], mathematics/computer sciences [21], [22], [23], [24], [25], and engineering [26], [27], [28], [29], [30]. However, we will need to be careful when using the term "virtual lab" since there is no set definition for "virtual lab."…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simulation laboratory is a kind of simulation experiment environment supported by computer software and hardware technology and realized by software development tools [2]. By developing a series of simulation experiment components to simulate and reproduce the experimental environment, experimental equipment and experimental process, the experimenter can get rid of the bondage of the actual experimental conditions, feel the experimental information interactively, and realize the experimental process in a near real way under more convenient and fast conditions [3]. In the simulation laboratory, the experimental objects and equipment are either reproduced or simulated vividly, and the experimental process is completely controlled by the experimenter [4].…”
Section: Introductionmentioning
confidence: 99%